Optimalisasi Pelayanan Administrasi Kependudukan Berbasis Eektronik Government (Studi Pada Inovasi Pelaku Paradewi oleh Dinas Kependudukan dan Pencatatan Sipil Kabupaten Mojokerto) - Nur Aulia Fadilah; Galih Wahyu Pradana; Muhammad Farid Ma’ruf; Deby Febriyan Eprilianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Population and Civil Registration Office of Mojokerto Regency introduced the Pelaku Paradewi innovation (Population Administration Services for Village or Urban Village Officers through a Website) to improve population administration services by bringing them closer to village communities. However, the implementation of this innovation has faced challenges, including slow service processes and frequent system errors. This study aims to analyze the optimization of e-government-based population administration services through the Pelaku Paradewi innovation at the Population and Civil Registration Office of Mojokerto Regency. This research employed a descriptive qualitative approach using Indrajit's (2016) theory of successful e-government implementation, which consists of three dimensions: Support, Capacity, and Value. The findings show that the implementation of Pelaku Paradewi has been relatively optimal despite several challenges. In the Support dimension, optimization is reflected through hierarchical regulations, an effective implementation team, consistently applied Standard Operating Procedures (SOPs), and multi-channel socialization, although information dissemination through social and mass media remains inconsistent. In the Capacity dimension, human resources are adequate in both quantity and competence, financial resources are managed efficiently through cross-sectoral collaboration despite limited budgetary independence, and infrastructure generally supports service delivery despite server instability and delays in data updates.